2014
DOI: 10.1038/ncb3007
|View full text |Cite
|
Sign up to set email alerts
|

The NBS1–Treacle complex controls ribosomal RNA transcription in response to DNA damage

Abstract: Chromosome breakage elicits transient silencing of ribosomal RNA synthesis, but the mechanisms involved remained elusive. Here we discover an in trans signalling mechanism that triggers pan-nuclear silencing of rRNA transcription in response to DNA damage. This is associated with transient recruitment of the Nijmegen breakage syndrome protein 1 (NBS1), a central regulator of DNA damage responses, into the nucleoli. We further identify TCOF1 (also known as Treacle), a nucleolar factor implicated in ribosome bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
229
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(260 citation statements)
references
References 33 publications
31
229
0
Order By: Relevance
“…While the use of γ-irradiation and laser microirradiation to induce DSBs has yielded conflicting results (Kruhlak et al 2007;Moore et al 2011;Larsen et al 2014), here we unequivocally demonstrated that DSBs within rDNA are sufficient to induce ATM-dependent inhibition of Pol I transcription. The introduction of the CRISPR/Cas9 allowed us to demonstrate that DSBs in both transcribed and nontranscribed regions of the rDNA repeat induce this response.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…While the use of γ-irradiation and laser microirradiation to induce DSBs has yielded conflicting results (Kruhlak et al 2007;Moore et al 2011;Larsen et al 2014), here we unequivocally demonstrated that DSBs within rDNA are sufficient to induce ATM-dependent inhibition of Pol I transcription. The introduction of the CRISPR/Cas9 allowed us to demonstrate that DSBs in both transcribed and nontranscribed regions of the rDNA repeat induce this response.…”
Section: Discussionmentioning
confidence: 60%
“…Other identified nucleolar targets include the Pol I transcription termination factor TTF1 and a component of the early pre-rRNA processing machinery, UTP14A. Finally, Treacle-a factor implicated in transcription and rRNA modification and an interaction partner of Nijmegen breakage syndrome protein 1 (NBS1)-is also an ATM target (Ciccia et al 2014;Larsen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we analyzed the recruitment of different DDR factors to upstream binding factor (UBF)-positive NCs. As recent articles reported the interaction of TCOF1 and NBS1, 33,34 we wanted to examine the role of TCOF1 in nucleolar DDR more closely. We show that TCOF1 interacts with chromatin modifiers such as CARM1 and HDAC1 following rRNA gene cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Next, it is plausible that nucleolus has important differences in its DDR when compared with non-nucleolar DNA repair. This is exemplified by the NBS1 TCOF1 interaction described recently, 33,34 but there are other examples. Nucleolin, an Editor's Highlight Figure 6.…”
mentioning
confidence: 99%